A Novel Method for Preparing Chromones via 1,2-Migration of α-Diazo-Flavanones - Sun, Minghao; You, Kejia; Chen, Nian; Ma, Baochun (Synlett, 2022)
A novel method for preparing chromones from α-diazo-flavanones has been developed. Good yields and regioselectivity are obtained through HCl catalysis and Rh2(Oct)4 catalysis. The chromone obtained can undergo a one-pot Diels–Alder reaction to synthesize flavanone propellane in high yield. Mechanisms about 1,2-migration under both catalysts are proposed.
Keywords: chromones; α-diazo-flavanones; propellanes; 1,2-migration; Diels–Alder reaction